Photo-enhanced field emission studies of tapered CdS nanobelts - Chavan, Padmakar G.; More, Mahendra A.; Joag, Dilip S.; Badadhe, Satish S.; Mulla, Imtiaz S. (2014 27th International Vacuum Nanoelectronics Conference (IVNC), 2014)
Field emission and photo-enhanced field emission characteristics of single crystalline tapered CdS nanobelts have been investigated. The turn-on field for the emission current density of similar to 0.1 mu A/cm(2) is found to be similar to 2.1 V/mu m, which is much lower than reported values for various CdS nanostructures. The photo-enhanced field emission current shows a reproducible photo-switching behavior with rise in current level nearly four times that of its initial preset value (similar to 1 mu A) which is found to be very remarkable. Possible mechanism of photo-enhanced field emission is discussed.
Keywords: Current stability; field emission; Nanobelts; Photoswitching